The Use of Letterland Method in Teaching Reading at Early Year Level to Pre-School Students in an Informal Education in Bandar Lampung - Alfiana Rochmah (Bandar Lampung University, 2015)
Letterland method was phonics based system that children learned about the correct sounds in English text. In every Letterlander had a story, action trick, singing a song and several activities thus it would make children improve their interest and encourage them in reading. This research also aimed at knowing the process of children learning in reading to early stage of reading and to know the way Letterland method would help children to be able to read. The subjects of this research were 3 to 9 years old in Bandar Lampung. They were purposefully selected as the data resource because they were in appropriate Letterland level. The instrument in conducting this research were observation and documentation from students worksheets. The results of the research concluded that the use of Letterland method to early year level would help and develop children learning process in reading.